Ordinance no. 1341, § 21, ASTORIA, CHARTER AND GENERAL ORDINANCES (J. S. Dellinger 1896). - (:unkn) unknown (My University, 1891)
Any person or persons who shall fire off or discharge any ordnance, gun, pistol, rifle or other fire-arm within the City Limits of Astoria, or any fire-works or fire-crackers of any kind or description, in that portion of the City west of Salmon street, north of Wall street or Court street and east of Madison street, shall be deemed guilty of a misdemeanor,
Keywords: DISCHARGE